Improving spatial accessibility to health care services in Cali, Colombia: stakeholder assessment of an innovative platform - Carmen J. Villamizar Jaimes; Luis Gabriel Cuervo; Eliana Martinez Herrera; Lucinda Cash-Gibson; Ciro Jaramillo; Joan Benach (Pan American Health Organization, 2024)
Objectives. To (i) ascertain stakeholders' perceptions of the contextual factors and resources necessary to successfully implement the AMORE platform, a tool that provides accessibility assessments for health care services, considering factors such travel time and traffic conditions, and (ii) identify potential barriers to and facilitators for enhancing spatial accessibility to health care services within the Colombian urban context. Methods. In this qualitative study, semi-structured interviews were conducted with a purposive sample of seven key stakeholders. The sample was drawn from individuals involved in development of policies in Colombia, service providers, and users, among others, who had expertise in the field. Interviews were conducted until saturation was reached. Results. The participants had positive views on the appearance of the AMORE platform, highlighting its user-friendly visualization. Suggestions were made about the variables used in the dashboard, the implementation of the platform, potential usage areas, and barriers and facilitators to implementation and use. Barriers included economic, political, and personnel challenges, while facilitators included creating a minimum viable product at a low cost and building interinstitutional and international cooperation. Conclusions. Innovations such as the AMORE platform have the potential to support decision-making processes across various sectors, including public policies and internal processes within private organizations, academia, and the community. However, implementing such a tool has financial, contextual and environmental challenges. The study identified key factors that were considered prerequisites for successfully implementing the AMORE platform in Colombian cities.